Elimination of Fusarium mycotoxin deoxynivalenol (DON) via microbial and enzymatic strategies: Current status and future perspectives - Tian, Ye; Zhang, Dachuan; Cai, Pengli; Lin, Huikang; Ying, Hao; Hu, Qian-Nan; Wu, Aibo (Trends in food science & technology, 2022)
Deoxynivalenol (DON) is an important Fusarium mycotoxin commonly detected in foods and feeds, which has drawn global attention because of its high contamination level and frequency. Applying microbial antagonists to inhibit fungal DON synthesis and detoxification of DON into low toxic metabolites are biological approaches to eliminate DON via an environment friendly manner. Therefore, it is essential to review the latest research work on Fusarium biocontrol and DON bio-detoxification. We summarized recent reported microbial and enzymatic methods for DON elimination. The microbial antagonists on Fusarium control and DON detoxification microbes/enzymes, as well as their control mechanisms were systematically reviewed. In addition, we highlighted the potentials of biological methods for DON elimination and discussed novel approaches for DON detoxification enzymes discovery guided by computational strategy. Successful cases of controlling DON producing fungi by microbial antagonists and detoxifying DON by microbes and enzymes were reported in the past several years, which would provide new opportunities to eliminate mycotoxin DON and promote large-scale usage of bio control-based methods. On the other hand, registration and technical difficulties in practical application should be comprehensively considered and solved in future. Additionally, we proposed a conceptual framework of combining the computational tools with multi omics approaches for DON detoxification enzymes discovery, which could provide a new foundation for future mycotoxin detoxification research. •DON is a food contaminant with high contamination level and frequency.•Microbial antagonists exhibit potentials on F. graminearum control.•Microbes and enzymes are desirable to dispose DON contaminated cereal grains.•Application of computational strategy towards DON detoxification enzyme screen is highlighted.